2021
DOI: 10.1002/fsn3.2297
|View full text |Cite
|
Sign up to set email alerts
|

The effect of food ration bar enriched with β‐alanine, L‐arginine, and Nigella sativa on performance and inflammation following intense military training: A double‐blind randomized clinical trial

Abstract: Background There are growing interests in using dietary supplements to improve athletic performance. This study aimed to evaluate the effect of the food ration bar enriched with β‐alanine, L‐arginine, and Nigella sativa on athletic performance and inflammation following intense military training. Methods This double‐blind, randomized, controlled clinical trial was conducted on 54 new cadets. Eligible participants were randomly assigned in a 1:1 ratio to receive food ration bars enriched with arginine (2 g/day)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…In a previous study, as a result of ingesting 3.4 g of β-alanine and 3.4 g of arginine per day for 2 weeks to elite soldiers, it was shown that TNF-α and CRP significantly decreased in the intake group [42], a study showing that IL-6 decreased and IL-10 increased immediately after resistance exercise as a result of administering 2 g of L-carnosine and 2 g of β-alanine per day for 2 weeks to the general public [43] also showed a decrease in the levels of IL-6 and TNF-α immediately after exercise in the intake group, consistent with the results of previous studies. Animal data also showed that injection of β-alanine to mice induced by myocardial ischemia/reperfusion significantly reduced TNF-α and IL-6 [44], and the injection of glutamine and β-alanine to mice treated with resistance exercise showed TNF-α, IL-6, IL-1β decreased, and IL-10 increased [45] which is consistent with the results of this study.…”
Section: Discussionmentioning
confidence: 93%
“…In a previous study, as a result of ingesting 3.4 g of β-alanine and 3.4 g of arginine per day for 2 weeks to elite soldiers, it was shown that TNF-α and CRP significantly decreased in the intake group [42], a study showing that IL-6 decreased and IL-10 increased immediately after resistance exercise as a result of administering 2 g of L-carnosine and 2 g of β-alanine per day for 2 weeks to the general public [43] also showed a decrease in the levels of IL-6 and TNF-α immediately after exercise in the intake group, consistent with the results of previous studies. Animal data also showed that injection of β-alanine to mice induced by myocardial ischemia/reperfusion significantly reduced TNF-α and IL-6 [44], and the injection of glutamine and β-alanine to mice treated with resistance exercise showed TNF-α, IL-6, IL-1β decreased, and IL-10 increased [45] which is consistent with the results of this study.…”
Section: Discussionmentioning
confidence: 93%
“…On the other hand, studies have shown that the buffering capacity of hydrogen ions is improved by increasing carnosine due to beta-alanine consumption, which may also be effective in increasing the aerobic capacity of players following beta-alanine consumption (31). Nevertheless, Gharaat et al and Hadi et al did not observe any improvement in maximal oxygen consumption following acute consumption of beta-alanine supplements (32,33). In the current research, the nature of the measurement and its time were different from the previous study.…”
Section: Discussionmentioning
confidence: 99%
“…The combination of L-alanine, L-arginine, and Nigella sativa improved anaerobic performance and decreased inflammation after strenuous physical activity. More long-term research on trained and untrained subjects is needed to confirm the cumulative/synergic effects of these substances (Hadi, 2021).…”
Section: Supplements For Performancementioning
confidence: 99%
“…There are a number of studies that have examined the effect of consumption of proteins and carbohydrates (PRO-CHO) on athletic performance parameters, running Time-to-Exhaustion (TTE), and running Time-Trial performance (TT) (Richardson, 2012), (Osterberg, 2008), (Rustad, 2016). A review of 43 trials comprising 326 subjects that consumed CHO-PRO compared with carbohydrates (CHO) only showed increased TT and TTE performances in the former compared with the latter (P < 0.05) (Hadi et al, 2021). However, not all studies reported a positive effect of CHO-PRO supplementation on TTE performance (Richardson, 2012), (Osterberg, 2008), and the variabilities could be due to different protocol designs and length of recovery across investigations (Beelen, 2010).…”
Section: Supplements For Performancementioning
confidence: 99%